PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT CHAROEN POKHAND JAYA FARM UNIT HATCHERY MANIS DI KABUPATEN TANGERANG - Difa Muhti Muhtar; Siti Aesah (Journal of Research and Publication Innovation, 2025)
This study aims to determine the influence of the physical work environment and discipline on employee performance at PT Charoen Pokphand Jaya Farm Unit Hatchery Manis in Tangerang Regency, both partially and simultaneously. The research employs a quantitative associative method, involving a population of 71 respondents with a saturated sample approach. Data analysis techniques include instrument tests, classical assumption tests, linear regression tests, correlation coefficient tests, determination coefficient tests, and hypothesis tests. The results indicate that the physical work environment has a positive effect on employee performance, with a correlation coefficient value of 0.494, signifying a moderately strong relationship. The determination coefficient contributes 24.4%, and the hypothesis test yields t (4.715) > (1.995). Discipline positively affects employee performance with a correlation coefficient of 0.618, signifying a strong relationship. The determination coefficient contributes 38.2%, and the hypothesis test yields t (6.530) > (1.995). Simultaneously, the physical work environment and discipline positively affect employee performance, with a regression equation of Y = 20.151 + 0.067 X1 + 0.442 X2. The correlation coefficient is 0.620, indicating a very strong relationship between the variables and employee performance. The determination coefficient contributes 38.4%, and the hypothesis test yields an F-value of (21.192) > (3.13).